Підсумки інтродукції Maclura рomifera (Rafin.) Schneid в умовах Правобережного Лісостепу України - Vitenko, V.A.; Shlapak, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The results of Maclura pomifera (Rafin.) Schneid introduction in the conditions of the Right-Bank Forest-Steppe zone of Ukraine are given. This species is determined to be perspective for using it in the ornamental horticulture of this region.